PENGARUH INTERVENSI KEBERSYUKURAN TERHADAP KESEJAHTERAAN PENYANDANG DISABILITAS FISIK - , wahyu dewanto; , Prof. Dr. Sofia Retnowati ([Yogyakarta] : Universitas Gadjah Mada, 2014)
People with physical disabilities may experience disappointment, sadness, anger, shame, hopelessness, worthless, and rejection on their condition caused by their physical condition. This may have impact on loss of function, roles, and self-image. The negative emotions and thoughts perceived and experienced, as well as the feeling that life would not be useful, may reduce their well-being. The gratitude intervention can be referred as treatment. This study was aimed to examine the effect of gratitude intervention towards people with physical disabilities well-being. The participants were two groups of people with physical disabilities (8 people for experimental group and 5 people for control group). The design of this study was untreated control group design with dependent pre-test and post-test samples. The similar treatment was also given for control group as a waiting list after intervention for experimental group. Well being was assessed using SPANE, PWS, and PTS. The result showed that there are significant differences in wellbeing score between experimental group and control group which are measured by SPANE U test -2,509, p=0,012. PWS U test -2,874, p = 0,04. PTS U test -2,590, p = 0,010.